Gut microbiota is involved in male reproductive function: a review - Lv, Shuya; Huang, Jingrong; Luo, Yadan; Wen, Yuhang; Chen, Baoting; Qiu, Hao; Chen, Huanxin; Yue, Tianhao; He, Lvqin; Feng, Baochun; Yu, Zehui; Zhao, Mingde; et al. (Frontiers in Microbiology, 2024)
Globally, approximately 8%-12% of couples confront infertility issues, male-related issues being accountable for 50%. This review focuses on the influence of gut microbiota and their metabolites on the male reproductive system from five perspectives: sperm quality, testicular structure, sex hormones, sexual behavior, and probiotic supplementation. To improve sperm quality, gut microbiota can secrete metabolites by themselves or regulate host metabolites. Endotoxemia is a key factor in testicular structure damage that causes orchitis and disrupts the blood-testis barrier (BTB). In addition, the gut microbiota can regulate sex hormone levels by participating in the synthesis of sex hormone-related enzymes directly and participating in the enterohepatic circulation of sex hormones, and affect the hypothalamic-pituitary-testis (HPT) axis. They can also activate areas of the brain that control sexual arousal and behavior through metabolites. Probiotic supplementation can improve male reproductive function. Therefore, the gut microbiota may affect male reproductive function and behavior; however, further research is needed to better understand the mechanisms underlying microbiota-mediated male infertility.